Sabo Dam Capacity Modelling Based on Its Performance Index - Rahadiansyah, Shakti; Limantara, Lily Montarcih; Bisri, M.; Prayogo, Tri Budi (Journal of Cultural Analysis and Social Change, 2025)
Capacity determined the advantage of a sabo dam in volcanic disaster management. By this research, the capacity function can be approached by infrastructure performance indexing. Its data are derived from eighty-five sabo dams that are installed in Mount Merapi in Java Island - Indonesia, and there is consisting of fifteen river system with upstream connected to its crater, i.e., Apu, Pabelan, Trising, Krasak, Blongkeng, Batang, Bebeng, Putih, Lamat, Senowo, Boyong, Kuning, Opak, Gendol, and Woro. The methodology is consisted of three steps of SEM PLS analysis for selecting the adequate indicators, followed by correlation analysis to improve the retained ruling indicators and generalized reducing gradient to obtain the weight of each indicator. The indicators of capacity modeling are arranged in three aspects as IC = 0.73F+0.07R+0.30S consecutively F is for physical, R is for regulative, and S is social aspect. The t-test shows the strong correlation valued as t = 0.05 ˂ t table = 1.29 means sabo dam capacity are dependable on nineteen indicators of: Spillway (f11), Main dam (f12), Wings (f13), Drip hole (f14), Sub dam (f15), Apron (f16), Apron’s wall (f17), Side dyke’s heap (f18), Dyke’s wall (f19), Dyke’s frame (f110), Dyke’s top (f111), Depth (f35), and Sabo dam capacity (f41) gathered in physical aspect, then Technical Recommendation (r23) in regulative aspect and social aspect including Occupation (s11), Economic (s12), Education (s13), Private share (s22) and Livestock (s34).